SURAU DAN TRADISI PERNASKAHANISLAM DI MINANGKABAU: STUDI ATAS DINAMIKA TRADISI PERNASKAHAN DI SURAU-SURAU DI PADANG DAN PADANG PARIAMAN* - Pramono Pramono (State Institute of Islamic Studies (IAIN) Palu, 2009)
Surau is a traditional institution of education in Minangkabau which has important role in developing Islam. In Islamic local discourse, surau became a center of order (tarîkah), the center for excellenceand for defending to criticize the another untrue ideology of Islam. In this context, syaikh from each surau write the manuscript to critisize the untruth ideology of Islam or social condition. There are four surau located in Padang and Padang Pariaman where many manuscripts can be found. The manuscripts are culturally important since they are related to the daily religious needs of the disciples of the order of Syattariyah in both places. This is related to the beliefs that to know about the guru, to posses the book, or to listen to the stories about the ulema, the guru of the order of Syattariyah are essential. Besides, the manuscripts are written to criticize opinions of the other Islamic schools whichare not appropriate according to the writer’s Islamic perception.Kata Kunci: tradisi pernaskahan Islam, surau, tarekat Syattariyah, Minangkabau